2017
DOI: 10.3389/fnagi.2017.00109
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity Disruption in Subjective Cognitive Decline and Mild Cognitive Impairment: A Common Pattern of Alterations

Abstract: Functional connectivity (FC) alterations represent a key feature in Alzheimer's Disease (AD) and provide a useful tool to characterize and predict the course of the disease. Those alterations have been also described in Mild Cognitive Impairment (MCI), a prodromal stage of AD. There is a growing interest in detecting AD pathology in the brain in the very early stages of the disorder. Subjective Cognitive Decline (SCD) could represent a preclinical asymptomatic stage of AD but very little is known about this po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
125
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(139 citation statements)
references
References 81 publications
12
125
1
1
Order By: Relevance
“…Besides, these results are compatible with previous work from our group reporting a dual pattern change in the FC profile of both MCI and SCD showing anterior hypersynchronization and FC reduction over similar posterior brain regions. 84 Interestingly, we did not find in the present work such a pattern in the nodal degree of SCD group, which could indicate that even though significant synchronization alterations are already present in this group, degree distribution seems to be still relatively preserved compared to MCI patients. Furthermore, SCD group exhibited increased nodal strength in a postcentral node in the theta band.…”
Section: Discussioncontrasting
confidence: 87%
“…Besides, these results are compatible with previous work from our group reporting a dual pattern change in the FC profile of both MCI and SCD showing anterior hypersynchronization and FC reduction over similar posterior brain regions. 84 Interestingly, we did not find in the present work such a pattern in the nodal degree of SCD group, which could indicate that even though significant synchronization alterations are already present in this group, degree distribution seems to be still relatively preserved compared to MCI patients. Furthermore, SCD group exhibited increased nodal strength in a postcentral node in the theta band.…”
Section: Discussioncontrasting
confidence: 87%
“…[32]. Moreover, SCD showed intermediate changes of DMN connectivity between MCI and HC[31][33]. Analogously, this study found that SCD showed intermediate changes of DMN-dominated FC/fALFF states, which was in line with previous reports.…”
supporting
confidence: 92%
“…However, many groups have also observed lower connectivity between these regions in individuals with SCD [18,[76][77][78][79]. Others have reported no difference from control [60], or intricate patterns of greater and lower functional connectivity in individuals with SCD [51][52][53][54][55], suggesting that a complex reorganization of processing responsibilities across network nodes may occur. Multifaceted patterns of increased and decreased connectivity between regions could reflect breakdown in processing within a subnetwork that shifts processing load to more intact components of the broader network.…”
Section: Brain Network Functional Connectivity In Subjective Cognitivmentioning
confidence: 99%